The Child's Right Act Simplified - Akin-Alabi, Olamide (Nigeria, 2020)
This is a book on the fundamental right of a child. It introduces how other people should relate with children and what children's rights are...
Keywords: Child Rights; Fundamental Rights; Juvenile Non-Fiction